An investigation of the effects of aspect ratio and opening on CSPSW and TSCSW. Issue 3 (25th February 2022) - Labibzadeh, Mojtaba; Bagheri, Mohsen; Khademalrasoul, Abdolghafour; Hossain, Khandaker M.A.
Abstract : Purpose: This paper aims to study, the effects of opening shape, size and position as well as the aspect (height-to-length) ratio on the shear capacity, stiffness, ductility and energy dissipation capacity of triple-skin profiled steel-concrete composite shear wall (TSCSW) and investigate and compare them to those of concrete-stiffened steel plate shear walls (CSPSW). Two kinds of opening, circular and square, with different sizes and positions and two aspect ratios of 1:1 and 3:1 are considered in the simulations. Design/methodology/approach: This study presents a novel TSCSW and compares its behavior with the existing CSPSW under the effect of monotonic and cyclic loadings. TSCSW is composed of three corrugated steel plates filled with concrete. The two external side plates are connected to the concrete core by means of several intermediate fasteners and the third one is an inner steel plate embedded within the concrete panel. The internal plate is a buckling restrained plate surrounded by concrete. This is the main superiority of TSCSW over other kinds of existing composite shear walls. Findings: The results show that the shear capacity and the energy dissipation capacity of the proposed composite wall, TSCSW, are respectively about 16 and 12% higher than those of CSPSW when there is no opening. If an opening is considered in the wall, as the size of the opening is increased, the shear capacity, stiffness, ductility and absorbed energy of the two walls are decreased similarly. The destructive effect of square openings on the performance of the walls is more than that of circular openings. Originality/value: This is an original work.